ANALISIS PEMILIHAN SERENTAK KETUA RW DAN KETUA RT KOTA MAKASSAR DITINJAU DARI ASPEK ETIKA POLITIK - Idris Patarai; Burhanuddin Burhanuddin; Akhir Saleh (Jurnal Pallangga Praja (JPP), 2020)
This study aims to analyze the election of RW and RT Chairpersons in terms of political ethics in Makassar City. The research method used isqualitative. Informants are voter or non-voters who live in six sub-districts. Based on geographical considerations, six districts were selected, namelyUjung Tanah, Makassar, Tamalate, Tamalanrea, Manggala and Rappocini. Data was extracted by researchers as human instruments, throughinterviews with informants. In addition, observation and documentation were also carried out. Data analysis proceeded by induction-interpretationconceptualization. The results showed that accountability for the legal aspects was largely ignored by the organizing agency such as therequirements of the 5% candidate, the completeness of the voting booths, and the completeness of the TPS administration. What is encouraging isthe enthusiasm of the community as a means of political education, it turns out that in general it can be well received, there does not appear to be anymeaningful friction, prolonged conflict and administrative demands that are compensatory and organizational. The legal legitimacy at the democraticparty is not relevant to the application of the rule of law based on values in the sociological principle, that in the existence of a statutory regulation,it should be interpreted as a need or an interest that can regulate society and felt as a demand that must be obeyed together. The regulation wasmade unilaterally by the city government without regard to the rules and legal values that live in the community